Fundamentals of combustion processes - McAllister, Sara; Chen, Jyh-Yuan.; Fernandez-Pello, A. C.; SpringerLink (Online service). (New York Springer, 2011)
Fundamentals of Combustion Processes serves students as a textbook for an upper-division undergraduate and graduate level combustion course in mechanical engineering. The authors focus on fundamental theory of combustion and provide a simplified discussion of basic combustion parameters and processes such as thermodynamics, chemical kinetics, ignition, diffusion, and pre-mixed flames. The text includes applications, example exercises, suggested homework problems, and videos of laboratory demonstrations.
Electronic reproduction.
Keywords: Combustion; Electronic book